Neptunium mononitride as a target material for Pu-238 production - Peruski, Kathryn M. (Frontiers in Nuclear Engineering, 2022)
Deep space exploration requires specialized sources for both thermal and power applications. Radioactive decay heat of plutonium-238 (238Pu) provides these sources in the form of radioisotope thermoelectric generators (RTGs). The 238Pu is produced via neutron capture reaction involving neptunium-237 (237Np) target material. Continual optimization of 237Np target materials and evaluation of potential alternative targets for production of 238Pu RTGs are advantageous for meeting ongoing space power system resource requirements. Current production of 238Pu for RTGs for the United States space program utilizes neptunium dioxide (237NpO2) targets; however, the use of neptunium mononitride (237NpN) presents an opportunity to increase the mass of 237Np per target compared to the dioxide form, as well as increase the thermal conductivity of the target. To assess the viability of a 237NpN target material, the material chemistry must be thoroughly evaluated, including synthesis methods and dissolution and reprocessing schemes. This review presents a summary of synthesis pathways for 237NpN based on published literature on actinide mononitrides. Specific literature on 237NpN is limited, necessitating evaluation of other actinide systems to gather parallels. This suggests a need for additional experimental studies on 237NpN. A particular limitation in the existing literature is a lack of information on the differences in material characteristics, such as morphology, particle size, and trace chemical impurities, as a function of synthesis method. These parameters may affect subsequent reactor performance or dissolution of irradiated targets. The evaluation of existing literature is presented with a focus on the efficacy of 237NpN targets for 238Pu production.